"Lean, mean" and feeling "powerful": Premature osteoporosis among young female athletes: Experiences and feminist sociological analyses - Sherlock, J.
This paper focuses on issues of being in control and being out of control of one's behaviour raised through research which gathered accounts of the experience of overtraining amongst young sportswomen. The initial purpose was to understand the processes involved in overtraining in order to educate others: young sportswomen, parents, teachers, coaches, doctors and sporting officials. Example from Triathlon.